The Essence Of Michelle Montin's Philosophical Views (Zien Journal of Social Sciences and Humanities, 2023)
The article examines the socio-philosophical views of Michel Montaigne, the greatest thinker of the European Renaissance, the great philosopher and humanist in the cultural development of 16th century France, his contribution to the development of the literary-philosophical and linguistic-cultural thought of his time